(untitled) (Bulletin of Pure and Applied Sciences-Chemistry, 2019)
The stress corrosion resistance of AL1100/SiC Nano Composites metal matrix composites (MMC’s) in high temperature acidic media has been evaluated using an autoclave. The liquid melt metallurgy technique using vortex method was used to fabricate MMC’s. SiC Nano Composites particulates of 50-80 μm in size are added to the matrix. AL1100 containing 2,4,6 weight percentage of SiC Nano Composites are prepared. Stress corrosion tests was conducted using weight loss method for different exposure time, normality and temperature of the acidic medium. The corrosion rates of composites was lower to that of matrix AL1100 alloy under all conditions.